1998
DOI: 10.1074/jbc.273.5.2631
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Ligand and Cell Surface Binding of Insulin-like Growth Factor-binding Protein-3

Abstract: The three deletion variants were incapable of binding ALS; but of the site-specific variants, the MDGEA mutant bound ALS with 90% lower affinity (K a ‫؍‬ 2.5 ؎ 0.9 liters/nmol) than seen for rhIGF-BP-3 (K a ‫؍‬ 24.3 ؎ 5.2 liters/nmol), whereas the RGD mutation had no effect on ALS affinity (K a ‫؍‬ 21.7 ؎ 4.5 liters/nmol). The ability of IGFBP-3 to associate with the cell surface was lost in variants lacking residues 185-264 and in the 228 KGRKR 3 MDGEA mutant. We conclude that residues 228 -232 of IGFBP-3 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 33 publications
7
112
1
1
Order By: Relevance
“…The IGFALS encodes the insulin‐like growth factor‐binding protein complex, acid labile subunit protein (ALS) which forms a ternary complex with IGF‐I and IGFBP‐3 (Firth et al ., 1998; Twigg & Baxter, 1998). Like in most GWAS, our analyses cannot establish which is the causative SNP or gene of a locus.…”
Section: Discussionmentioning
confidence: 99%
“…The IGFALS encodes the insulin‐like growth factor‐binding protein complex, acid labile subunit protein (ALS) which forms a ternary complex with IGF‐I and IGFBP‐3 (Firth et al ., 1998; Twigg & Baxter, 1998). Like in most GWAS, our analyses cannot establish which is the causative SNP or gene of a locus.…”
Section: Discussionmentioning
confidence: 99%
“…(35). However, we have also shown that this IGFBP-3 mutant is unable to bind at the cell surface (38), leading to the speculation that transport to the nucleus may be blocked at the level of the plasma membrane rather than at the level of entry into the nucleus. To address this issue, we compared nuclear uptake of wild-type and mutant IGFBP-3 (in cells were the plasma membrane had been permeabilized) using the fully reconstituted in vitro nuclear transport assay.…”
Section: ј-Agcaggatccagcctcgccgtccatggaaggtttgcactgctttcmentioning
confidence: 88%
“…human IGFBP-3 and IGFBP-3[ 228 KGRKR 3 MDGEA] were produced by a replication-deficient adenovirus-mediated expression system, as described previously (37). IGFBP-3 was purified from conditioned media by IGF-I affinity chromatography and reverse-phase high pressure liquid chromatography (38). In studies requiring fluorescently labeled IGFBP-3, the protein was conjugated to dichlorotriazinylaminofluorescein I HCl as described previously for Cy3 (35).…”
Section: Are Modulated By a Family Of Igf-binding Proteins (Igfbps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of 14, 36, and 48 amino acid residues from the carboxyl terminus appeared to have no effect on IGF binding, whereas removal of a further 14 amino acid residues dramatically reduced IGF binding. Other studies have shown that removal of most or all of the carboxyl-terminal domains of IGFBP-3 (16,41), , and IGFBP-5 (8) reduces IGF binding significantly.…”
Section: Discussionmentioning
confidence: 99%